Inoculation concentration modulating the secretion and accumulation pattern of exopolysaccharides in desert cyanobacterium Microcoleus vaginatus. (17th May 2020) - Qian, Long; Wu, Li; Yang, Lie; Zhang, Zulin
Abstract: Cyanobacterial exopolysaccharides (EPS) accumulated during microalgal cultivation have significant application potential in antioxidation, pharmaceutical products, and so on. Inoculation concentration strongly affects the cultivation cost, biomass, and EPS accumulation. In this study, a high‐EPS‐excreted desert cyanobacterium Microcoleus vaginatus was isolated, and the effects of inoculation concentration on biomass, photosynthetic activity, and EPS accumulation were explored. The results showed that the original fluorescence ( F o ) provided a good indication to cyanobacterial biomass, when Chl‐a concentration was lower than 10 mg L −1 . Inoculation concentration significantly affected cyanobacterial biomass and EPS concentration ( P < 0.001), whereas did not affect photosynthetic activity ( F v / F m ; P > 0.05). The two fractions of EPS, capsular exopolysaccharides (CPS) and released exopolysaccharides (RPS) were strongly affect by inoculation concentration. Other than forming thick sheath (CPS) surrounded the filaments, M . vaginatus excreted higher proportions of RPS to culture medium, and the ratio of RPS to CPS ranged from 1.08 to 1.58 depending on the inoculation concentration. Additionally, although the biomass and EPS accumulation increased with inoculation concentration, the increasing inoculation concentration did not bring to the proportionate increase of the final biomass and EPS yield. Altogether, comprehensively considering the EPS yield and productivity, inoculation concentration of 0.04 mg Chl‐a L −1 is recommended for M. vaginatus to produce EPS, with an EPS yield of 94.32 mg L −1 and EPS productivity of 184.86 mg (mg Chl‐a) −1 L −1 d −1 at the end of experiment. Abstract : The isolation, cultivation and exopolysaccharides pattern of desert cyanobacterium Microcoleus vaginatus .